Implementasi Kurikulum Merdeka Terkait Profil Pelajar Pancasila pada Mata Pelajaran PAI di SMP Negeri 12 Cimahi - NURUL Latifah; Dedih Surana; Ayi Sobarna (Bandung Conference Series: Islamic Education, 2023)
Abstract. In the independent curriculum related to Pancasila student profiles, there are main dimensions related to Islamic Religious Education. And this is one of the answers to answer the challenges of the times, where even though the times are continuing to occur, religious character education in Indonesia is the main point of all aspects. Because religious character education is the main foundation in Indonesia to create Indonesian citizens who believe, fear God and have noble character. Kemdikbudristek pours character education for the Indonesian people into the independent learning curriculum which has various dimensions in it or commonly known as the Pancasila student profile. The first dimension of the Pancasila student profile has the meaning of character education for students towards their religion which is based on Pancasila which needs to be realized during the learning process. This study aims to determine the program, process, assessment, and supporting factors and obstacles of the independent curriculum related to the profile of Pancasila students in PAI subjects at SMP Negeri 12 Cimahi. The research method used in this research is a case study with a qualitative research approach, and for the process of collecting data using interview techniques, observation and documentation. The results of this study indicate that the implementation of the independent curriculum related to the profile of Pancasila students on the dimension of faith and piety to God Almighty, and having noble character in PAI subjects at SMP Negeri 12 Cimahi has not been realized optimally because activities that apply the profile of Pancasila student dimensions of faith and piety to God Almighty, and Having a noble character has only been realized in intra-curricular activities, extracurricular reading and writing of the Qur'an (BTQ), and the habituation of school culture, while co-curricular activities have not been realized. Even so, educators at SMP Negeri 12 Cimahi continue to maximize the activities that are already in school so that the implementation of the independent curriculum related to the profile of Pancasila students can be realized properly. Keywords: Implementation of the Independent Curriculum Related to Pancasila Student Profiles, Islamic Religious Education. Abstrak. Dalam kurikulum merdeka terkait profil pelajar pancasila terdapat dimensi utama yang berkaitan dengan Pendidikan Agama Islam. Dan inilah salah satu jawaban untuk menjawab tantangan perkembangan zaman, dimana meskipun perkembangan zaman terus terjadi namun pendidikan karakter keagamaan di negara Indonesia menjadi poin utama dari segala aspek. Sebab pendidikan karakter keagamaan menjadi suatu landasan utama di negara Indonesia untuk menciptakan warga Indonesia yang beriman, bertakwa kepada Tuhan YME dan berakhlak mulia. Kemdikbudristek menuangkan pendidikan karakter untuk bangsa Indonesia pada kurikulum merdeka belajar yang memiliki berbagai dimensi didalamnya atau biasa disebut dengan profil pelajar pancasila. Dimensi pertama dari profil pelajar pancasila memiliki makna pendidikan karakter peserta didik terhadap agamanya yang berlandaskan pada Pancasila yang perlu diwujudkan selama proses pembelajaran. Penelitian ini bertujuan untuk mengetahui program, proses, penilaian, dan faktor pendukung dan hambatan dari kurikulum merdeka terkait profil pelajar pancasila pada mata pelajaran PAI di SMP Negeri 12 Cimahi. Adapun metode penelitian yang digunakan dalam penelitian ini adalah studi kasus dengan pendekatan penelitian kualitatif, dan untuk proses pengumpulan data menggunakan teknik wawancara, observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa penerapan kurikulum merdeka terkait profil pelajar pancasila dimensi beriman bertakwa kepada Tuhan YME, dan berakhlak mulia pada mata pelajaran PAI di SMP Negeri 12 Cimahi belum terealisasi dengan maksimal karena kegiatan yang menerapkan profil pelajar pancasila dimensi beriman bertakwa kepada Tuhan YME, dan berakhlak mulia baru terealisasikan pada kegiatan intrakurikuler, ekstrakurikuler Baca Tulis Al-qur‟an (BTQ), dan pembiasaan budaya sekolah, sedangkan pada kegiatan kokurikuler belum terealisasikan. Meskipun demikian, pendidik di SMP Negeri 12 Cimahi terus memaksimalkan kegiatan yang sudah ada di sekolah agar penerapan kurikulum merdeka terkait profil pelajar pancasila bisa terealisasikan dengan sebagaimana mestinya. Kata Kunci: Implementasi Kurikulum Merdeka Terkait Profil Pelajar Pancasila, Pendidikan Agama Islam.